Maskulinitas dan Peran Ayah dalam Film ‘KAKA BOSS’: Kajian Representasi Media - Sugitha, Dhea Moufdi; Fajarini, Sri Dwi (ARKANA: Jurnal Komunikasi dan Media, 2025)
This study aims to examine the representation of masculinity and fatherhood in the film “Kaka Boss” through a media representation analysis approach. As a product of popular culture, film functions not only as entertainment but also as a symbolic space that shapes, reproduces, and even challenges social norms, including constructions of masculinity. Using a qualitative approach and semiotic analysis method, this research identifies how the father figure is portrayed in terms of power relations, emotional expression, and domestic roles. The analysis reveals that the film presents a father figure whose masculinity is not entirely traditional, yet still does not fully transcend gender stereotypes. This representation highlights the complexity of fatherhood amid expectations to be firm, hardworking, yet also gentle and caring. The study affirms that media plays a vital role in redefining masculinity in the modern era.